Sistem Pelayanan Kenaikan Pangkat Pegawai Negeri Sipil Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Batu Bara - Suhendri Suhendri (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The development of information technology has significantly transformed government administration, including the promotion system for Civil Servants (PNS). The National Civil Service Agency (BKN) has developed the Civil Service Administration Information System (SIASN) to expedite the PNS promotion process digitally. However, implementing this system still faces several challenges, such as a lack of employee understanding, limited human resources, and technical issues in system usage. This study aims to analyze the effectiveness of the promotion service system implemented by the Personnel and Human Resource Development Agency (BKPSDM) of Batu Bara Regency. The study employs interviews, observations, and document analysis to identify key issues in the promotion process and provide recommendations to enhance service efficiency and quality. The findings indicate that although a digital system has been adopted, its implementation still encounters obstacles, such as incomplete data, inadequate technological infrastructure, and employees' limited ability to operate the system. Therefore, improving employee training, strengthening technological infrastructure, and refining administrative policies are recommended measures to enhance the effectiveness of the PNS promotion service system in Batu Bara Regency.